2014
DOI: 10.1242/jeb.104182
|View full text |Cite
|
Sign up to set email alerts
|

Following the Sun: a mathematical analysis of the tracks of clock-shifted homing pigeons

Abstract: We analysed the tracks of clock-shifted pigeons from six releases to determine how they cope with the conflict between their sun compass and other navigational cues. Time-lag embedding was used to calculate the short-term correlation dimension, a parameter that reflects the complexity of the navigational system, and with it, the number of factors involved. Initially, while pigeons were still at the release site, the short-term correlation dimension was low; it increased as the birds left the site, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…On their way home, they re-determine their home course, – this is evident because pigeons return in spite of large initial deviations caused by release site biases [4] or experimental manipulations like shifting their internal clock (e.g. [31][33]). Keeton [4], trying to explain the existence of a pronounced bias and its local constancy, suggested that an unusual distribution of ‘map’ factors at the respective site led the pigeons off the direct route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On their way home, they re-determine their home course, – this is evident because pigeons return in spite of large initial deviations caused by release site biases [4] or experimental manipulations like shifting their internal clock (e.g. [31][33]). Keeton [4], trying to explain the existence of a pronounced bias and its local constancy, suggested that an unusual distribution of ‘map’ factors at the respective site led the pigeons off the direct route.…”
Section: Discussionmentioning
confidence: 99%
“…For sites beyond 25 km, we only considered the last 25 km; for the additional sites, we excluded the first 2.5 km to eliminate spurious effects from low short-term correlation dimension in the vicinity of the release point (see e.g. [33]). …”
Section: Methodsmentioning
confidence: 99%